Digital Single Market and the EU Competition Regime: An Explanation of Policy Change. Issue 1 (2nd January 2022) - Cini, Michelle; Czulno, Patryk
ABSTRACT: Although the EU competition regime is well-established and highly effective, EU policy actors may still need to rethink their tried and tested approach to competition regulation. This is what happened in the context of the European Commission's planned regulation of online platforms, embodied (in part) within the Digital Markets Act. This article reviews the interplay of the EU's competition regime with its relatively new Digital Single Market strategy to ask how a traditional ex-post approach to competition regulation came to be supplemented by a (proposed) ex-ante regulatory approach. Informed by the literature on policy change, the article examines the policy context, the Commission's experience gained in dealing with competition cases, and the input of lobbyists, advocacy groups and experts, to explain this shift in Commission policy.